The Perception and Motivation of the Second Year Students of English Education Department of University of Islam Malang in Taking Online Learning Activities - Moh. - Ruzin (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aims to investigate the second year EFL university students’ perceptions and motivations experiencing online learning system amidst the Covid-19 pandemic. This study used qualitative descriptive approach with descriptive research as the research design. The participants of this study were 22 second year students of English Education Department, University of Islam Malang. To investigate students’ perceptions and motivations, the researcher used two instruments, online questionnaire and interview, as the methods of collecting data. The findings of this study showed that the EFL students’ perceptions and motivations experiencing online learning system differed from each other. Firstly, students’ perceptions were positive in some aspects such as the role of the lecturers in explaining learning materials and were negative in terms of the effectiveness of online learning system since they faced some difficulties such as unstable networks, less interaction, and less control, etc. Secondly, some of the students were motivated; they always motivate their selves to study even though the situation was uncomfortable. However, some others were less motivated since the online learning system has never been felt before, and also the pandemic has been running for a long time; the students felt bored with the situation and even lost their motivations. Keywords: Students’ Perceptions, Students’ Motivations, Online Learning